168k views
3 votes
Help fill out the proof

Help fill out the proof-example-1
User MarisP
by
5.9k points

1 Answer

5 votes

Answer:

Step V: Transitive property of Inequality

Step VI: Subtraction Property of Inequality

Explanation:

In Step IV, the RHS of t=both the sides are equal.

So, they equated the LHS of both the sides.

This is the transitive property of equality which states that if a = b and c = b then a = c.

In this case, a =
$ \angle {m_1} + \angle {m_2}  $

b = 180⁰

c =
$ \angle {m_2} + \angle {m_3} $

Consequently,
$ \angle {m_1} + \angle {m_2} = \angle {m_2} + \angle {m_3} $

In step VI,
$ \angle {m_2} $ is subtracted on both the sides. So, this is called as Subtraction Property of Equality.

User SmitM
by
5.9k points